Study of nutritional status of adolescent girls in a rural area of a district of Maharashtra - Nair, Abhilasha; Doibale, Mohan K.; Kuril, Bina M.; Domple, Vijay K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescence is the transition period between childhood and adulthood where rapid physical, mental, emotional and social development takes place. Adolescent girls are at greatest risk for nutrient deficiency and it badly affects their overall development. With this background this study was conducted to study some aspects of the socio-demographic profile and to assess the nutritional status of adolescent girls by anthropometry in a rural area of a district. Methods: It was a community based cross sectional study conducted during January 2015 to June 2015 in 10 villages of a district. 583 adolescent girls were interviewed using pre designed, pretested questionnaire and anthropometric examination was done. Results were analyzed with the help of Microsoft Excel 2007 and SPSS version 16.0 statistical software. Results: Mean age of the study population was 13.95±2.48 years. Majority (63.12%) were Hindu and belonged to nuclear family (54.72%). 45.63% were educated up to high school level. Most of the girls belonged to socio economic class IV (45.46%). The prevalence of underweight and stunting in this study was 36.54% and 48.37% respectively. Statistically significant association was found between underweight and marital status of adolescent girls (p=0.029). The association of age group, religion and educational status with stunting was statistically significant (p<0.05). Mean BMI of the total 583 study subjects was 17.66±2.42 kg/m2. The prevalence of thinness was 18.87% in this study, significantly associated with religion, type of family and socioeconomic status (<0.05). Conclusions: Since the prevalence of under nutrition was high among adolescent girls in our study, appropriate health education and nutrition intervention should be directed towards them to improve their nutritional status.